Analysis of Changes in Habitat Suitability of the Javan Leopard (Panthera pardus melas, Cuvier 1809) on Java Island, 2000–2020 - As’ary, Muhammad; Setiawan, Yudi; Rinaldi, Dones (Diversity (Basel), 2023)
The Javan leopard is an apex predator whose distribution is limited to the island of Java and Nusakambangan Island, and it is classified as an endangered species. The forest habitat of the Javan leopard is subject to annual damage, which causes a decrease in its quality and suitability as a habitat for this species. This study aimed to determine the changes in the suitability of the Javan leopard habitat from 2000 to 2020 and the variables affecting it. A habitat suitability analysis was performed using the MaxEnt application. The data included coordinate points and environment variables. The variables included the distance from rivers, undisturbed tropical forests, degraded forests, permanent water, shrubs, farms, plantations, and settlements. The model produced an AUC value of 0.812, indicating the model was good. In the 2000 model year, the highly suitable habitat area of the Javan leopard was 2481.38 km2, the suitable habitat area was 2630.763 km2, and the unsuitable area was 7790.155 km2. In the 2020 model, the area of highly suitable habitat was 1429.647 km2, the area of suitable habitat was 2379.344 km2, and the area that was not suitable was 9093.081 km2. Primary forest was the variable that contributed most to the model.